GanoCare™ fertilization effects on growth and suppression of basal stem rot disease of oil palm seedlings - Rebitanim, Nur Akmal (2016)
The oil palm industry is on alert for the basal stem rot (BSR) disease. The BSR which is caused by Ganoderma boninense, is the major disease of oil palm and is a serious threat to the palm oil production in Malaysia. One of the ideal solutions to manage BSR disease is through supplementation of nutrients. With no definitive cure at the present, thus this study introduced a new fertilizer technology called GanoCare™, as an effort to suppress BSR incidence in oil palm. The GanoCare™ fertilizer was produced from powdered oil palm empty fruit bunches (EFB) incorporated with beneficial elements. The optimum levels of GanoCare™ from two different application frequencies for the growth of oil palm was determined in a six-month nursery trial, and subsequently extended in the field trial for 21 months. All growth and physiological parameters evaluated were positively correlated with GanoCare™ levels up to a certain level. Two rates at 10 g/palm for every month application and 30 g/palm for every three months application were identified as optimum levels for the growth of oil palm seedlings. In the field, the optimum levels were at 100 g/palm for every month application and 300 g/palm for every three months application. The effect of optimized rate of GanoCare™ 1 on growth, physiological and BSR disease suppression were assessed in the nursery stage using sitting (bait) technique, in which the treatments added were CT (control), T1 (pre-treatment with 10 g/month), T2 (pre-treatment with 30 g/three months), T3 (pre-treatment and continuous treatment with 10 g/month) and T4 (pre-treatment and continuous treatment with 30 g/three months). A follow up in the field stage was carried out for 21 months to test on severity of Ganoderma using baiting technique under natural condition. The treatments were similar as in the nursery stage, however with some alterations to suit the condition of the experiment. In nursery, the application of GanoCare™ 1 significantly enhanced the height, girth, frond count, total leaf area, chlorophyll content, photosynthesis rate, fresh and dry weight of oil palm seedlings when compared to the control. Despite some modifications done to the treatments, the results from the field trial validate the pathological results from the nursery, in which both experiments similarly showed that application of GanoCare™ was able to suppress the incidence of BSR disease compared to the control seedlings. For both studies in nursery and field, the disease reduction was higher for seedlings given pretreatment and continuous treatment (T3 and T4) compared to the seedlings that were pre-treated only (T1 and T2), suggesting that continuous application is required to provide maximum protection from Ganoderma disease, and that pre-treatment alone was not sufficient to allow the development of a strong defense system in the seedlings. Combination of pre-treatment and continuous treatment with 30 g of GanoCare™ at three-month intervals (T4) was the most effective treatment in both nursery and field by reducing the BSR disease by 77.78 and 82.36%, respectively.